Molecular Mechanisms of Ferroptosis and Its Roles in Hematologic Malignancies - Zhao, Yan; Huang, Zineng; Peng, Hongling (Frontiers in Oncology, 2021)
Cell death is essential for the normal metabolism of human organisms. Ferroptosis is a unique regulated cell death (RCD) mode characterized by excess accumulation of iron-dependent lipid peroxide and reactive oxygen species (ROS) compared with other well-known programmed cell death. It has been currently recognized that ferroptosis plays a rather important role in the occurrence, development, and treatment of traumatic brain injury, stroke, acute kidney injury, liver damage, ischemia-reperfusion injury, tumor, etc. Of note, ferroptosis may be explained by the expression of various molecules and signaling components, among which iron, lipid, and amino acid metabolism are the key regulatory mechanisms of ferroptosis. Meanwhile, tumor cells of hematological malignancies, such as leukemia, lymphoma, and multiple myeloma (MM), are identified to be sensitive to ferroptosis. Targeting potential regulatory factors in the ferroptosis pathway may promote or inhibit the disease progression of these malignancies. In this review, a systematic summary was conducted on the key molecular mechanisms of ferroptosis and the current potential relationships of ferroptosis with leukemia, lymphoma and MM, etc. It is expected to provide novel potential therapeutic approaches and targets for hematological malignancies.